Exploring the international linkages of the euro area: a global VAR analysis - Stéphane Dées; Filippo di Mauro; Hashem Pesaran; Vanessa Smith (European Central Bank (ECB), 2005)
This paper presents a quarterly global model linking individual country vector errorcorrecting models in which the domestic variables are related to the country-specific foreign variables. The global VAR (GVAR) model is estimated for 26 countries, the euro area being treated as a single economy, over the period 1979-2003. It advances research in this area in a number of directions. In particular, it provides a theoretical framework where the GVAR is derived as an approximation to a global unobserved common factor model. It develops a sieve bootstrap procedure for simulation of the GVAR as a whole to test the structural stability of the regression coefficients and error variances, and to establish confidence bounds for the impulse responses. Finally, in addition to generalized impulse responses, the paper also considers the use of the GVAR for "structural" impulse response analysis.
Keywords: C32; E17; F47; 330; Global interdependencies; global macroeconomic modeling; Global VAR (GVAR); impulse responses; Konjunkturzusammenhang; Makroökonometrie; VAR-Modell; Schätzung; Eurozone; Welt; EU-Staaten; USA